Physician centricity in the deployment of digital solutions for neurological conditions. (February 2022) - Jones, Graham B; Freeman, Jason; Mann, Allison; Khanna, Amit
The widespread deployment of telemedical approaches to managed care during the CoV2 pandemic has provided an opportunity for clinicians to engage in the development and refinement of this mode of delivery. This also represents a pivotal moment to help effect a paradigm shift in how new and more sophisticated digital health services are designed and delivered with the caregiver playing a guiding role. Building on momentum this way can allow the fuller potential of digital health to be realized by focusing on "end user pull" which balances the omnipresent "technology push" of the consumer product and medical device industries. Perhaps nowhere is this more critical than in the care of neurological illnesses where patient–provider interactions must be managed frequently and rely on a complex battery of data measures. The emergent role of the physician-entrepreneur can be envisioned, complimenting established physician-scientist career paths and represents a timely and opportune moment to refine medical education curricula.